Farming games in the cozy aesthetic a fantasy of dreams of a simple life - Mazurkiewicz, Adam (Replay. The Polish Journal of Game Studies, 2024)
The article is devoted to the trend of farm games, which can be described using the aesthetics of cozy / “coziness”. The countryside life they create is based on cultural phenomena (mainly slow cinema and idyllic images derived from popular songs). What characterizes cozy games is creating the impression of slowness and putting relationships above competition or achieving the intended goal. For this reason, the stages of “life” on the farm, which make up the player’s functioning in the game – sowing, waiting for the harvest, and harvest itself – become the goal in themselves, constituting a source of satisfaction thanks to their repetition. The cyclicality inherent in the routine corresponds to the renewal proper to ritual time. The participation in this act of the user of the game allows them to enter this time in order to take part in a ritual that gives additional meaning to what is monotonous. The aim of the article is to present farm games as a realization in the digital space of a phantasm about a “simple life,” which is a response to the social reality dynamically changing due to the influence of technology. At the same time, this dream is an artistic manifestation of a broader existential project, which is the slow life trend.